No Harm No Foul Behavior and Consumption Motivation Among Indonesian Students - Juneman Abraham; Ammeta Firly Maulida (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2015)
Large scale corruption could start from everyday unethical daily behavior. Due to its “everyday” nature, the effects of such behavior often go unnoticed. This research examines the no harm no foul behavior (NHNF) as a behavior that is located in the “gray area” but can be perceived as unethical by some people. The psychological predictors of the behavior will be investigated, i.e. utilitarian and hedonic motivation in a world of consumption. Participants were late adolescent students recruited through convenience sampling technique in the Greater Area of Jakarta, the Capital of Indonesia (148 males, 72 females; Mage = 20.055 years old, SDage = 1.181 years). It was found that utilitarian motivation can predict the evaluation of NHNF as an unethical behavior in a positive direction while hedonic motivation was not found to be able to predict it. Suggestions to improve the NHNF measurement and implications also issues to be considered when applying the results of the study will be discussed at the end of this article.